Merrily we roll along [videorecording (DVD)] - Sondheim, Stephen; Tunick, Jonathan (Sony Pictures Home Entertainment, 2026)
"In a bold new cinematic interpretation, Merrily We Roll Along charts the turbulent relationship between composer Franklin Shepard and lifelong friends Mary and Charley. "--